Implementasi Metode Pembelajaran Aktif dalam Pembelajaran Pendidikan Agama Islam di Sekolah Menengah: Tantangan dan Peluang - Wahid, Latiful; Rohman, M. Zainur; Pahrudin, Agus (Cetta: Jurnal Ilmu Pendidikan, 2024)
This research aims to examine the implementation of active learning methods in planning PAI learning systems in secondary schools. This research uses a qualitative approach (Field Research) with data collection techniques of direct observation in the field and in-depth interviews with PAI teachers who are involved in lesson planning. Data were analyzed using thematic analysis methods to identify patterns and main findings. The research results show that the implementation of active learning methods in planning PAI learning systems in secondary schools faces unique challenges and opportunities. The main challenges include the availability of limited resources, teachers' understanding of the concept of active learning, and the integration of Islamic religious values in the learning approach. However, there are also opportunities to utilize the wealth of local resources and community involvement to enrich PAI learning. This research concludes by highlighting the importance of training and mentoring for PAI teachers in developing lesson planning skills oriented towards active learning methods. Apart from that, this research also emphasizes the need for collaboration between education stakeholders, including schools, teachers, students and local communities, in increasing the effectiveness of implementing active learning methods in PAI learning in secondary schools.